A hard carbon material based on a carboxyl structure regulator and a preparation method and application thereof
Patent Information
- Application Number
- CN202611100952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]本发明的目的是提供一种基于羧基结构调控剂的硬碳材料及其制备方法和应用,针对现有生物质硬碳改性工艺污染大、无法同步实现闭孔增殖与碳缺陷修复、电化学综合性能差的技术缺陷
1、本发明全程不使用浓强酸、强碱、高毒有机溶剂,浸渍后直接干燥,无需水洗、中和、溶剂回收工序,无酸碱、含盐有机废液排放;三废处理成本相比传统酸碱活化降低,生产工时缩短,设备无强腐蚀,适配连续化工业生产。
Smart Images

Figure CN123002813A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hard carbon materials technology, and in particular to a hard carbon material based on a carboxyl structure modifier, its preparation method, and its application. Background Technology
[0002] Sodium resources are abundant globally and inexpensive to mine. Sodium-ion batteries share a similar energy storage mechanism with lithium-ion batteries, demonstrating immense industrial potential in large-scale energy storage power stations, low-speed new energy vehicles, and grid-connected energy storage for wind and solar renewable energy. The anode material directly determines the reversible capacity, rate charge / discharge capability, and cycle life of sodium-ion batteries. Traditional graphite carbon has narrow interlayer spacing, making it difficult for sodium ions to stably and reversibly insert and extract, thus failing to meet the requirements of sodium-ion batteries. Hard carbon is currently the only anode carbon material for sodium-ion batteries with large-scale commercial potential.
[0003] Biomass-based hard carbon uses agricultural and forestry waste such as peanut shells, rice husks, and straw as precursors. It has advantages such as renewable raw materials, wide availability, and low production costs. However, pure biomass hard carbon obtained by direct high-temperature carbonization has inherent defects: insufficient number of closed pores inside the material, too many open pores and carbon vacancies / edge defects on the surface, which directly leads to low initial coulombic efficiency, poor high current rate performance, and rapid cycle capacity decay.
[0004] Existing technologies for improving the pore structure of hard carbon in biomass fall into three main categories, each with irreconcilable technical shortcomings: Strong acid / base activation pretreatment: This involves using strong corrosive agents such as hydrochloric acid, sulfuric acid, KOH, and phosphoric acid to etch biomass, generating numerous interconnected open pores and significantly increasing carbon defect density. However, this treatment necessitates the use of large amounts of pure water for washing and alkali neutralization, resulting in high-salt, high-acid / alkaline wastewater, leading to high waste treatment costs and severe equipment corrosion. Furthermore, this approach only improves specific capacity, with limited improvement in coulombic efficiency in the first week.
[0005] Inorganic metal salt activation (zinc chloride, zinc nitrate): High-temperature templates for metal salts create pores, but metal oxides / elements remain inside the carbon matrix, requiring acid washing to remove metal impurities, which also generates salt-containing waste liquid; activation is mainly based on opening pores, making it difficult to generate a large number of closed sodium storage cavities, and unable to simultaneously repair carbon layer defects.
[0006] Hydrothermal modification of single organic acids (citric acid, tartaric acid): The process is relatively mild, but it lacks metal catalytic sites, can only slightly crosslink to repair a small number of carbon defects, has no template site occupation to create closed pores, the improvement in closed pores is extremely low, and the improvement in electrochemical performance is not obvious.
[0007] Meanwhile, existing static impregnation pretreatment can only change the surface composition of biomass and cannot dynamically and synchronously control carbon layer rearrangement, pore evolution and carbon defect repair during segmented carbonization. There has long been a technical bias in the industry: if the number of closed pores is to be increased, high-concentration metal salt activation must be used, and metal residues will inevitably be accompanied by acid washing process; if a low-defect flat carbon layer is pursued, it will lead to pore collapse and a decrease in sodium storage capacity. The two cannot be achieved at the same time.
[0008] Based on the aforementioned shortcomings, the industry urgently needs to develop a green preparation method for biomass hard carbon that is gentle, produces no waste liquid, and allows for dynamic and synergistic control of microporous structure and carbon defects. Summary of the Invention
[0009] The purpose of this invention is to provide a hard carbon material based on a carboxyl structure regulator, its preparation method, and its applications, addressing the technical shortcomings of existing biomass hard carbon modification processes, such as high pollution levels, inability to simultaneously achieve closed-pore proliferation and carbon defect repair, and poor overall electrochemical performance. This invention produces no acid or alkali wastewater and requires no water washing or neutralization. It utilizes the synergistic effect of segmented pyrolysis of carboxyl-based organometallic salts to simultaneously construct a closed sodium storage cavity and catalyze the formation of a regularized carbon layer to reduce defects, resulting in a biomass hard carbon anode material with high initial efficiency, high reversible capacity, and long-term cycle stability.
[0010] To achieve the above objectives, the present invention provides a method for preparing hard carbon materials based on carboxyl structure modifiers, comprising the following steps: S1 Biomass Raw Material Pretreatment: Biomass waste is washed, dried, crushed and sieved to obtain biomass powder with a particle size of 0.1μm~50μm; S2 Carboxyl-Regulated Impregnation: Biomass powder is impregnated with a carboxyl-containing structure regulator in an aqueous phase or water-alcohol mixture at a constant temperature. After impregnation, solid-liquid separation is performed and the mixture is directly dried. The carboxyl-containing structure regulator is zinc citrate, citric acid aqueous solution, or a combination of citric acid and zinc source. S3 Two-Stage Carbonization: The dried biomass powder is first pre-carbonized in an inert atmosphere, and then carbonized at high temperature to obtain hard carbon materials.
[0011] Preferably, in step S1, the biomass raw material is selected from one or more of the following: peanut shells, rice shells, coconut shells, walnut shells, apricot shells, bamboo, wood chips, straw, sugarcane bagasse, corn cobs, fruit shells, fruit kernels, and plant fibers.
[0012] Preferably, in step 2, the amount of carboxyl-containing structure regulator added is 1% to 20% of the biomass raw material mass.
[0013] Preferably, in step 2, the zinc source includes one or more of zinc oxide, zinc acetate, zinc nitrate, zinc chloride, and zinc carbonate.
[0014] Preferably, in step S2, the impregnation includes the following methods: Method 1: Direct impregnation treatment with zinc citrate. Disperse biomass powder in water or a water-alcohol mixture, add zinc citrate or a structure modifier containing zinc citrate, and ensure that zinc citrate is in full contact with the biomass. The mixing temperature is 15-80℃ and the mixing time is 4-24 hours. Method 2: Independent impregnation pretreatment with citric acid aqueous solution at 50-80℃. The concentration of citric acid aqueous solution is 0.05-2 mol / L. Biomass powder is added to citric acid aqueous solution and stirred, impregnated or refluxed at 50-80℃. The treatment temperature of citric acid aqueous solution is 50-80℃, and the treatment time is 2-12 hours. The solid-liquid ratio is 1g:10-50mL. Method 3: Citric acid is combined with a zinc source to generate zinc citrate complex in situ within the biomass channels.
[0015] Preferably, in step S3, the pre-carbonization temperature is increased to 350~650℃ at a rate of 0.5-10℃ / min and held for 0.5~5h; the high-temperature carbonization temperature is increased to 1200~1400℃ at a rate of 1-10℃ / min and held for 0.5~10h.
[0016] A hard carbon material based on a carboxyl structure regulator is prepared according to the above-described preparation method.
[0017] Preferably, the hard carbon material has a disordered, bent, amorphous stacked structure with an initial coulombic efficiency of ≥91%.
[0018] This invention also provides an application of hard carbon materials based on carboxyl structure modifiers, used as negative electrode active materials for sodium-ion batteries, potassium-ion batteries, lithium-ion batteries, or electrochemical capacitors.
[0019] The advantages and beneficial effects of the above-mentioned hard carbon material based on carboxyl structure regulator, its preparation method, and its application are as follows: 1. This invention does not use concentrated strong acids, strong alkalis, or highly toxic organic solvents throughout the entire process. After impregnation, the product is directly dried without the need for washing, neutralization, or solvent recovery processes. There is no discharge of acid, alkali, or salt-containing organic waste liquid. Compared with traditional acid-alkali activation, the cost of waste treatment is reduced, production time is shortened, the equipment is not highly corrosive, and it is suitable for continuous industrial production.
[0020] 2. This invention relies on the multiple effects of segmented pyrolysis of carboxyl metal organosalts to generate a large number of closed sodium storage cavities in situ without etching to create surface interconnected open pores. At the same time, it catalyzes the regularization of the carbon layer to reduce defects. This solves the long-standing technical conflict in the prior art that "creating pores will inevitably increase defects, and low defects will inevitably lead to the loss of closed pores".
[0021] 3. This invention comprehensively improves the overall electrochemical performance, meeting commercialization indicators, and achieves high initial coulombic efficiency: the optimized sample's initial efficiency is increased from 85% in the unmodified sample to over 91%, reducing irreversible capacity loss and lowering battery pre-charge costs; the closed pores provide a large number of low-pressure sodium storage sites, increasing sodium storage capacity to 0.3Ag. -1 Reversible capacity ≥345mAhg under certain conditions -1 Excellent rate performance: 0.3~3Ag -1 Capacity retention ≥88% in the high current range, excellent sodium ion diffusion kinetics; ultra-long cycle stability: 0.3Ag -1 3Ag -1 The capacity decay is less than 8% after 1,000 cycles, and the carbon skeleton and closed-cell structure are stable.
[0022] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0023] Figure 1 The images shown are SEM images of the hard carbon materials prepared in the embodiments and comparative examples of the present invention, where A is Comparative Example 1, B is Example 2, and C is Example 1. Figure 2 The XRD pattern of the hard carbon material prepared in Example 1 of this invention; Figure 3 The figures show a comparison of nitrogen adsorption-desorption curves and pore size distributions of the hard carbon materials prepared in the comparative examples and embodiments, where A is the nitrogen adsorption-desorption curve and B is the pore size distribution comparison figure. Figure 4 The hard carbon material of Example 1 at 0.3Ag -1 Long-cycle performance curves at current density; Figure 5 The hard carbon material of Example 1 at 3.0 Ag -1 Long-cycle performance curves at high current density; Figure 6 The hard carbon material of Example 1 was used in the range of 0.3~3.0 Ag. -1 Range performance curve; Figure 7 The above are comparison graphs of charge-discharge curves for the examples and comparative examples, where a is comparative example 1, b is example 2, and c is example 1. Detailed Implementation
[0024] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0025] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0026] The following examples are not intended to limit the invention, but are only for illustration. Unless otherwise specified, the experimental methods used in the following examples are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0027] Example 1 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects peanut shells rich in cellulose, hemicellulose and lignin as carbon precursors. The peanut shells are washed with water to remove impurities, dried in an oven, mechanically crushed and screened to control the particle size to 45μm.
[0028] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is zinc citrate. The amount of regulator added is 10% of the biomass feedstock mass.
[0029] For direct zinc citrate impregnation treatment, 100g of sieved peanut shell powder is dispersed in 1L of deionized water, 10g of zinc citrate is added, and the mixture is stirred at a constant temperature for thorough impregnation; the mixing temperature is 50℃; and the impregnation time is 12h.
[0030] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 80℃; only a small amount of water washing is performed under strict control of metal residue requirements.
[0031] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 2℃ / min to 500℃, hold for 2 hours. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0032] High-temperature carbonization stage: heating rate 5℃ / min to 1300℃, holding for 3 hours; Zn in the system 2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0033] When zinc citrate or zinc-containing modifiers are used, Zn species can play roles such as template occupancy, local catalysis of carbon layer rearrangement, and leaving closed-pore cavities during carbonization. When citric acid is used, it can promote dehydration crosslinking, gas release, and carbon skeleton rearrangement during heat treatment and carbonization, which is beneficial for closed-pore construction and defect control.
[0034] The carboxyl structure regulator plays multiple roles during in-situ decomposition in pyrolysis: First, the regulator melts into a liquid state at approximately 100-150℃, uniformly wetting the interior of the biomass material. As the temperature rises to the pre-carbonization stage at 400℃, it decomposes, releasing gases such as CO2, which are trapped within the carbon layer, forming nascent closed-pore structures. Subsequently, during further carbonization at 600℃ and high-temperature carbonization at 1300℃, the metal oxides / metals in the regulator catalyze local carbon layer rearrangement, repairing structural defects, while the metal elements evaporate, leaving behind closed-pore cavities. This process achieves dynamic control over carbon layer rearrangement, pore structure evolution, and defect repair, thus simultaneously achieving the dual goals of "increasing the number of closed pores" and "reducing carbon defects," which is impossible with traditional pretreatment methods.
[0035] Example 2 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects peanut shells rich in cellulose, hemicellulose and lignin as carbon precursors. The peanut shells are washed with water to remove impurities, dried in an oven, mechanically crushed and screened to control the particle size to 30μm.
[0036] S2 is modified by aqueous impregnation with a carboxyl-containing structure modifier, which is an aqueous solution of citric acid. The concentration of the citric acid aqueous solution is 0.5 mol / L.
[0037] The solid-liquid ratio of biomass powder to citric acid aqueous solution is 1g:20mL. Peanut shell powder is added to the solution, and the mixture is stirred / refluxed at 60℃ for 6 hours. After filtration, it is dried directly at 80℃.
[0038] Citric acid molecules undergo complexation, dehydration, and esterification cross-linking with the hydroxyl and ether bonds of biomass; the treated solid is directly dried without the addition of alkali for neutralization, resulting in no saline waste liquid.
[0039] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 60℃ for 20 hours; only a small amount of water washing is performed under strict control of metal residue requirements.
[0040] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 2℃ / min to 500℃, hold for 2 hours. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0041] High-temperature carbonization stage: heating rate 5℃ / min to 1300℃, holding for 3 hours; Zn in the system 2+Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0042] Example 3 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects peanut shells rich in cellulose, hemicellulose and lignin as carbon precursors. The peanut shells are successively washed with water to remove impurities, dried in an oven, mechanically crushed and screened to control the particle size to 20μm.
[0043] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is a combination of citric acid and zinc source.
[0044] Citric acid and zinc acetate were added to the pure water system simultaneously and stirred at 60°C for 10 hours to generate zinc citrate complex in situ; after filtration, the mixture was dried at 80°C.
[0045] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 2℃ / min to 450℃, holding for 1.5h. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0046] High-temperature carbonization stage: heating rate 5℃ / min to 1350℃, holding for 2 hours; Zn in the system 2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0047] Example 4 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects wood chips as carbon precursor. The wood chips are successively washed with clean water to remove impurities, dried in an oven, mechanically crushed, and screened and graded to control the particle size to 15μm.
[0048] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is zinc citrate. The amount of regulator added is 5% of the biomass feedstock mass.
[0049] For direct impregnation treatment with zinc citrate, 100g of sieved wood chip powder is dispersed in 1L of deionized water, 5g of zinc citrate is added, and the mixture is stirred at a constant temperature to ensure thorough impregnation; the mixing temperature is 60℃; and the impregnation time is 10h.
[0050] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 80℃; only a small amount of water washing is performed under strict control of metal residue requirements.
[0051] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 5℃ / min to 350℃, hold for 3 hours. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0052] High-temperature carbonization stage: heating rate 2℃ / min to 1400℃, holding for 5h; Zn in the system 2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0053] Example 5 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects walnut shells as carbon precursors. The walnut shells are washed with clean water to remove impurities, dried in an oven, mechanically crushed, and screened and graded to control the particle size to 45μm.
[0054] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is zinc citrate. The amount of regulator added is 15% of the biomass feedstock mass.
[0055] For direct zinc citrate impregnation treatment, 100g of sieved walnut shell powder was dispersed in 1L of deionized water, 15g of zinc citrate was added, and the mixture was stirred at a constant temperature for thorough impregnation; the mixing temperature was 70℃; and the impregnation time was 18h.
[0056] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 80℃; only a small amount of water washing is performed under strict control of metal residue requirements.
[0057] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 8℃ / min to 600℃, holding for 4 hours. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0058] High-temperature carbonization stage: heating rate 3℃ / min to 1200℃, holding for 5h; Zn in the system2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0059] Example 6 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment uses corn cobs as carbon precursors. The corn cobs are washed with clean water to remove impurities, dried in an oven, mechanically crushed, and screened and graded to control the particle size to 10μm.
[0060] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is zinc citrate. The amount of regulator added is 20% of the biomass feedstock mass.
[0061] For direct zinc citrate impregnation treatment, 100g of sieved corn cob powder is dispersed in 1L of deionized water, 20g of zinc citrate is added, and the mixture is stirred at a constant temperature for thorough impregnation; the mixing temperature is 80℃; and the impregnation time is 20h.
[0062] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 80℃; only a small amount of water washing is performed under strict control of metal residue requirements.
[0063] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 6℃ / min to 650℃, held for 4 hours. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0064] High-temperature carbonization stage: heating rate 10℃ / min to 1250℃, holding for 6 hours; Zn in the system 2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0065] Example 7 A method for preparing hard carbon materials based on carboxyl structure modifiers includes the following steps: S1 biomass raw material pretreatment selects bamboo as carbon precursor. The bamboo is washed with clean water to remove impurities, dried in an oven, mechanically crushed, and screened and graded to control the particle size to 50μm.
[0066] S2 is modified by aqueous impregnation with a carboxyl-containing structure regulator, which is zinc citrate. The amount of regulator added is 15% of the biomass feedstock mass.
[0067] For direct impregnation treatment with zinc citrate, 100g of sieved bamboo powder is dispersed in 1L of deionized water, 15g of zinc citrate is added, and the mixture is stirred at a constant temperature to ensure thorough impregnation; the mixing temperature is 45℃; and the impregnation time is 15h.
[0068] After impregnation, the solid-liquid separation is directly achieved by filtration / centrifugation without water washing or strong alkali neutralization, and dried at 80℃; only a small amount of water washing is performed under strict control of metal residue requirements.
[0069] S3 two-stage inert atmosphere carbonization involves placing the dried modified biomass precursor in a tube furnace and introducing a nitrogen inert atmosphere. A weak reducing atmosphere or vacuum environment can also be used. The process employs a two-stage carbonization step-by-step approach. Pre-carbonization stage: Heating rate 6℃ / min to 400℃, holding for 1.5h. The regulator melts and penetrates the biomass skeleton at low temperature, thermally decomposes to release CO2 gas, and is encapsulated by the carbon layer to form a closed-cell prototype.
[0070] High-temperature carbonization stage: heating rate 3℃ / min to 1400℃, holding for 6 hours; Zn in the system 2+ Catalytic carbon layer rearrangement fills carbon vacancies and edge defects; zinc is completely vaporized and volatilized at high temperature, permanently preserving a closed nano-sized sodium storage cavity inside the carbon matrix, thus obtaining the target hard carbon material.
[0071] Comparative Example 1 Unlike Example 1, the preparation method does not include step S2; the rest is the same as in Example 1.
[0072] The performance of the samples prepared in Examples 1-2 and Comparative Example 1 was tested.
[0073] like Figure 1 As shown in Figure A, the initial sample exhibits severe particle breakage and significant fine fragmentation. The carbon sheet edges show numerous wrinkles and hollow defects, and the surface is covered with fine debris. Figure 1 As shown in Figure B, after modification with citric acid impregnation alone, the particle integrity was slightly improved, but a large number of small, broken particles still remained. Figure 1 As shown in Figure C, the carbon particles with complete flaky outlines and regular sizes were controlled by zinc citrate carboxyl metal salt composite. The proportion of fine powder was significantly reduced, the carbon matrix surface was smooth and flat, without a large number of through corrosion pores and metal salt agglomeration particles. This proves that the two-step carbonization process of carboxyl metal organic salt can repair carbon layer defects and stabilize the carbon skeleton structure. At the same time, the zinc component is completely volatilized without residue at high temperature.
[0074] Figure 2The X-ray diffraction (XRD) pattern of the biomass-based hard carbon material prepared by zinc citrate composite regulation in Example 1 is shown. The pattern shows a typical diffuse broad diffraction peak of the carbon (002) crystal plane at 2θ≈24° and a weak broad peak of the (100) crystal plane at 2θ≈43°. There are no sharp diffraction peaks characteristic of graphite, which proves that the obtained material is amorphous hard carbon with disordered stacking of carbon layers and large interlayer spacing, which is suitable for sodium ion insertion. No characteristic diffraction peaks of zinc, zinc oxide, or organometallic salt precursors are found in the full scanning range, which confirms that the zinc component is completely vaporized and volatilized at high temperature during the carbonization process. The finished product does not require acid washing to remove impurities, and there is no discharge of acid, alkali, or salt waste liquid throughout the process.
[0075] This invention relies on the covalent anchoring of polycarboxylated zinc citrate with the hydroxyl groups of biomass, combined with a two-stage segmented temperature-controlled carbonization process. Combined with the characterization evidence of no metal impurity peaks in the XRD pattern, it proves that metal components can be completely removed without the need for water washing and acid washing processes. At the same time, the diffuse broad diffraction peaks verify that the material has a highly disordered hard carbon crystal structure, simultaneously achieving the triple effects of closed sodium storage pore construction, carbon defect repair, and green, waste-free preparation. This synergistic effect cannot be obtained by simply superimposing existing technologies.
[0076] Figure 3 A represents the nitrogen adsorption-desorption isotherms for three groups of hard carbon samples. Figure 3 In the figure, B represents the differential distribution curve of the BJH aperture. The green curve represents Comparative Example 1, the orange curve represents Example 2, and the purple curve represents Example 1.
[0077] As can be seen from the isotherms, all three groups of samples exhibited type IV adsorption isotherms. Example 2 had the largest total adsorption pore volume, with a large number of 2-20 nm interconnected mesopores and micropores. Example 1 had a moderately reduced total open pore volume, significantly reducing 5-20 nm interconnected mesopores and retaining only a small number of 2-4 nm surface micropores. Comparative Example 1 had the lowest overall pore volume, with scarce sodium storage channels. The pore size distribution curves confirmed that the two-stage carbonization process of the carboxyl metal salt of this invention can suppress the formation of interconnected open pores and directionally construct closed nanopores that are undetectable by nitrogen within the carbon matrix, achieving an ideal hard carbon pore structure for sodium storage with "low open pores and high closed pores." This can effectively reduce irreversible decomposition of the electrolyte and improve the first coulombic efficiency.
[0078] Figure 4 Example 1: Hard carbon anode at a current density of 0.3 Ag -1 The following is a long-cycle capacity curve of 200 cycles; the horizontal axis represents the number of charge-discharge cycles, and the vertical axis represents the reversible sodium storage capacity of the electrode; the initial reversible capacity of the sample can reach 360 mAh·g. -1After 200 cycles, the capacity retention rate reached 95.7%; the curve showed no rapid capacity drop throughout, proving that the hard carbon skeleton and the internal closed sodium storage cavity structure prepared by the two-stage carbonization process of carboxylic metal salt of this invention have excellent stability, few carbon defects, weak irreversible side reactions of electrolyte, and ultra-long cycle life, meeting the requirements for long-term use of large-scale energy storage devices.
[0079] Figure 5 Example 1: Hard carbon anode at a high current density of 0.3 Ag -1 The following is an ultra-long cycle capacity curve of 3000 cycles; the horizontal axis represents the number of charge-discharge cycles, and the vertical axis represents the reversible sodium storage capacity of the electrode; the initial reversible capacity of the sample under high current conditions can reach approximately 300 mAh·g. -1 After 3000 continuous high-rate charge and discharge cycles, the capacity retention rate is still 80%; the curve shows only slight capacity decay in the early stage, and the decay rate is gradual in the middle and late stages, without a cliff-like drop in capacity. This confirms that the hard carbon prepared by the two-stage carbonization process of carboxylic metal salt in this invention has excellent high-current sodium intercalation and deintercalation kinetics and ultra-long cycle structural stability, making it suitable for high-power energy storage and fast-charging sodium-ion battery application scenarios.
[0080] Figure 6 The graph shows the rate performance curve of the hard carbon anode in Example 1; the horizontal axis represents the number of charge-discharge cycles, and the vertical axis represents the reversible sodium storage capacity of the electrode. The current density gradient is 0.03 Ag. -1 0.06Ag -1 0.15Ag -1 0.3Ag -1 0.6Ag -1 1.5Ag -1 3.0Ag -1 After the test, the value will be reverted to 0.3Ag. -1 The sample was at 0.03 Ag. -1 Reversible capacity up to 365 mAh·g under low current -1 Upgraded to 3.0Ag -1 It still maintains 280 Ah·g under high current. -1 Stable capacity; when the current density drops back to 0.3Ag -1 The capacity was fully restored afterward, with no permanent irreversible capacity decay, which proves that the sodium ion diffusion kinetics performance of the hard carbon material of this invention is excellent. The carbon skeleton and the closed sodium storage cavity structure are stable and do not collapse during the high and low rate switching process, and are suitable for various application scenarios such as low-speed energy storage and high-power fast charging.
[0081] Figure 7 This is a comparison of the charge-discharge curves of the three hard carbon samples of this invention in the first three cycles at a current density of 0.1C. Figure 7 In the example 'a', 'a' represents comparative example 1. Figure 7 b is Example 2. Figure 7c) represents Example 1; the blue curve represents cycle 1, the yellow curve represents cycle 2, and the red curve represents cycle 3 of charge / discharge; the initial sample had an initial coulombic efficiency (ICE) of 85% and a reversible capacity of only 282 mAh·g. -1 Example 2: Sample ICE increased to 87%, reversible capacity 385 mAh·g -1 Example 1: Initial coulombic efficiency reaches 91%, reversible capacity reaches 425 mAh·g. -1 All three groups of samples exhibited a low-pressure sodium storage platform with hard carbon characteristics in the 0~0.2V range. The low-pressure platform capacity ratio of Example 1 was significantly higher than that of the other two groups. The curves of the second and third cycles highly overlapped, proving that the hard carbon sodium intercalation and deintercalation prepared by this invention has excellent reversibility. The above results confirm that the two-stage carbonization process of carboxyl metal organosalt can simultaneously increase the closed pores of closed sodium storage, reduce the open pores and carbon defects on the carbon surface, and improve the reversible sodium storage capacity and the first coulombic efficiency.
[0082] Therefore, this invention employs a hard carbon material based on a carboxyl structure regulator, its preparation method, and its application, addressing the technical shortcomings of existing biomass hard carbon modification processes, such as high pollution levels, inability to simultaneously achieve closed-pore proliferation and carbon defect repair, and poor overall electrochemical performance. This invention produces no acid or alkali wastewater and requires no water washing or neutralization. It utilizes the synergistic effect of segmented pyrolysis of carboxyl-based organometallic salts to simultaneously construct a closed sodium storage cavity and catalyze the formation of a regular carbon layer to reduce defects, resulting in a biomass hard carbon anode material with high initial efficiency, high reversible capacity, and long-term cycle stability.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing hard carbon materials based on carboxyl structure modifiers, characterized in that, Includes the following steps: S1 Biomass Raw Material Pretreatment: Biomass waste is washed, dried, crushed and sieved to obtain biomass powder with a particle size of 0.1μm~50μm; S2 Carboxyl-Regulated Impregnation: Biomass powder is impregnated with a carboxyl-containing structure regulator in an aqueous phase or water-alcohol mixture at a constant temperature. After impregnation, solid-liquid separation is performed and the mixture is directly dried. The carboxyl-containing structure regulator is zinc citrate, citric acid aqueous solution, or a combination of citric acid and zinc source. S3 Two-Stage Carbonization: The dried biomass powder is first pre-carbonized in an inert atmosphere, and then carbonized at high temperature to obtain hard carbon materials.
2. The method for preparing a hard carbon material based on a carboxyl structure regulator according to claim 1, characterized in that: In step S1, the biomass raw materials are selected from one or more of the following: peanut shells, rice husks, coconut shells, walnut shells, apricot shells, bamboo, wood chips, straw, sugarcane bagasse, and corn cobs.
3. The method for preparing a hard carbon material based on a carboxyl structure regulator according to claim 1, characterized in that: In step 2, the amount of carboxyl-containing structure regulator added is 1% to 20% of the biomass raw material mass.
4. The method for preparing a hard carbon material based on a carboxyl structure regulator according to claim 1, characterized in that: In step 2, the zinc source includes one or more of zinc oxide, zinc acetate, zinc nitrate, zinc chloride, and zinc carbonate.
5. The method for preparing a hard carbon material based on a carboxyl structure regulator according to claim 1, characterized in that: In step S2, the impregnation includes the following methods: Method 1: Direct impregnation treatment with zinc citrate. Disperse biomass powder in water or a water-alcohol mixture, add zinc citrate or a structure modifier containing zinc citrate, and ensure that zinc citrate is in full contact with the biomass. The mixing temperature is 15-80℃ and the mixing time is 4-24 hours. Method 2: Independent impregnation pretreatment with citric acid aqueous solution at 50-80℃. The concentration of citric acid aqueous solution is 0.05-2 mol / L. Biomass powder is added to citric acid aqueous solution and stirred, impregnated or refluxed at 50-80℃. The treatment temperature of citric acid aqueous solution is 50-80℃, and the treatment time is 2-12 hours. The solid-liquid ratio is 1g:10-50mL. Method 3: Citric acid is combined with a zinc source to generate zinc citrate complex in situ within the biomass channels.
6. The method for preparing a hard carbon material based on a carboxyl structure regulator according to claim 1, characterized in that: In step S3, the pre-carbonization temperature is increased to 350~650℃ at a rate of 0.5-10℃ / min and held for 0.5~5h; the high-temperature carbonization temperature is increased to 1200~1400℃ at a rate of 1-10℃ / min and held for 0.5~10h.
7. A hard carbon material based on a carboxyl structure modifier, characterized in that: It is prepared according to the preparation method described in any one of claims 1-6.
8. A hard carbon material based on a carboxyl structure modifier according to claim 7, characterized in that: The carbon layers of the hard carbon material exhibit a disordered, bent, amorphous stacked structure with an initial coulombic efficiency of ≥91%.
9. The application of a hard carbon material based on a carboxyl structure modifier according to any one of claims 7-8, characterized in that: Used as a negative electrode active material in sodium-ion batteries, potassium-ion batteries, lithium-ion batteries, or electrochemical capacitors.
